Diversity Patterns In The Implementation Of Zikr And Prayer Readings After Congregational Prayers (Qs Al-a'raf [7]: 205) - Ahmad Zabidi; Hamnah Hamnah; Sri Sunantri; Maulana Maulana; Alkadri Alkadri; Hadari Hadari (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2023)
Prayer is a Muslim's obligation, so there is no reason to abandon it except for women who are menstruating, postpartum and after giving birth. However, in the implementation of congregational prayers in the community there are differences, especially in terms of reciting zikr and prayers in congregation led by the imam. There are priests after congregational prayers reading zikr and prayers together with the congregation and there are priests after congregational prayers reading zikr and prayers in silence (reading slowly). This research is a type of qualitative library research. The data source is secondary data originating from library sources. The analytical method uses content analysis, to uncover problems in understanding differences. This difference is due to the existence of propositions or texts from the Quran and hadis which explain whether or not it is necessary to read dhikr and prayers in congregation. In fact, this difference does not need to be widely debated, but the lessons and benefits of this difference should be taken. So that the harmony and unity of Muslims is maintained and well maintained without prioritizing excessive desires and attitudes in understanding Islamic teachings, especially in terms of carrying out congregational prayers after fardhu prayers.